"A matter of trust": Perception of morality increases willingness to help through positive emotions. (April 2020) - Cuadrado, Isabel; López-Rodríguez, Lucía; Constantin, Andreea A.
Moroccans are still the lowest rated immigrants in Spain. This research analyses the relationships between different dimensions of stereotypes (i.e., morality, sociability, and competence), positive emotions, and facilitation behavioural tendencies between Spaniards and Moroccans. Specifically, this work aims to explore whether the three stereotype dimensions play distinct roles in predicting helping behavioural tendencies through emotions, with a focus on the distinctive role of morality. Three studies are presented. In Study 1, Spanish adolescents assessed Moroccan immigrants. Study 2 considered the minority perspective by analysing Moroccans' stereotypes, emotions, and behavioural tendencies toward Spaniards. Study 3 experimentally tested the effect of the stereotype dimensions on positive emotions and facilitation behavioural tendencies in a sample of Spaniards. The results showed a consistent pattern: perceived morality always indirectly predicted facilitation behavioural tendencies through positive emotions, regardless of the perspective analysed (i.e., majority/minority), age of participants (i.e., adults/adolescents), or design (i.e., correlational/experimental).